Changing small towns - Trócsányi, András; Máté, Éva (Journal for Geography, 2024)
The Journal for Geography is excited to announce a call for papers for a special thematic issue focusing on "small towns." We are inviting researchers and practitioners from all fields of geography and other spatial sciences to contribute original research articles, reviews, and case studies that explore various dimensions of small towns across the globe. This issue aims to delve into the diverse aspects of small towns as spatial-administrative units, local communities, demographic categories, heritage and built-up areas, or specific development issues.